Seroprevalence of Hepatitis B, Hepatitis C and Human Immunodeficiency Virus Among Multitransfused Thalassaemic Children in Dhaka, Bangladesh (Bangladesh Journal of Child Health, 2014)
Background: Thalassaemia is a congenital hemolytic disease caused by defective globin chain synthesis of haemoglobin and largely treated by repeated blood transfusions. Transfusion-transmitted infections still make a great challenge in the management of patients with thalassaemia major. The most important worldwide transfusion transmitted infections (TTI) are hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV). Despite concern about a possible increase in the incidence of these infections there are no recent data about the prevalence of HBV, HCV and HIV from Bangladesh. Objectives: To evaluate the prevalence of hepatitis B, hepatitis C and human immunodeficiency virus in multi-transfused thalassaemia patients (MTP), to identify the possible risk factors and to evaluate the effect of compulsory screening of blood to prevent these infections. Methodology: This cross-sectional study was conducted during 2011 to 2012 on 100 consecutive multi-transfused thalassaemic patients who were interviewed using a structured questionnaire and tested for serological markers of hepatitis B virus (HBsAg), hepatitis C virus (Anti-HCV) and human immunodeficiency virus (Anti-HIV 1+2). Results: The overall prevalence of HCV, HBV, HIV and co-infection among (MTP) were 31%, 3%, 0% and 1%, respectively. Children who developed infection had a higher incidence of receiving transfusion from professional donors or unknown donors than the non-infected ones. Infected children had a higher frequency of receiving transfusions without screening and receiving more number of transfusions than their counterpart. Other non-transfusion related (NTR) risk factors such as surgical operation, dental procedures, needle stick injury were significantly higher in patients who acquired transfusion transmitted infections (TTI). Conclusions: HCV infection was the most prevalent transfusion transmitted infection (TTI) among multi-transfused thalassaemia patients (MTP) and remains a major health problem for these patients. Children who received transfusion from professional donors and received unscreened blood had more chance of getting infection with transfusion transmitted infection. DOI: http://dx.doi.org/10.3329/bjch.v37i3.18618 Bangladesh J Child Health 2013; Vol.37(3): 146-153